أهمية فهم مقاصد السنة النبوية في تطوير الاقتصاد الإسلامي والمجتمعات المعاصرة - مهاوات, عبد القادر; لعناني, محمد (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدّراسة إلى استقراء مقاصد نصوص السّنّة النّبويّة باعتبارها مصدرًا من مصادر الشّريعة الإسلاميّة، وبيان مدى أهميّتها في تطوير الاقتصاد الإسلاميّ والمجتمعات المعاصرة؛ وذلك بالاعتماد على منهجَيِ الوصْف والتّحليل حال عرْض الجوانب النّظريّة للموضوع ومناقشة جزئيّاته. وقد خلُصت هذه الدّراسة إلى أنّ الفهْم المقاصديّ السّليم لنصوص السّنّة النّبويّة الخاصّة بالاقتصاد والمجتمع يُسهم في تكييف القضايا الاقتصاديّة المعاصرة، وتطوير أدواتٍ ماليّةٍ واقتصاديّةٍ ذات كفاءةٍ عاليةٍ، ويكشف عن العلاقة التّكامليّة بين النّصوص النّبويّة الاقتصاديّة والاجتماعيّة، ممّا يسمح بتطوير منظومة اقتصاديّة إسلاميّة متكاملة ومسؤولة اجتماعيًّا. The present study aimed to extrapolate the intends sunnah texts as a source of Islamic Sharia, and demonstrate the intentional inmportance of economic and social sunnah texts in building of islamic economy and Contemporary societies, by using the descriptive and analytical approach in describing theoretical aspects of the study and discussing its parts. This study concluded that the Correct intentional understanding of economic and social sunnah texts contribute to adapting contemporary economic issues, developing highly efficient financial tools and revealing the complementary relationship between economic and social sunnah texts, thus allowing the establishment of an Islamic and socially responsible economic system.
مقال
Keywords: مقاصد شرعية؛ سنة نبوية؛ اقتصاد إسلامي؛ مجتمعات معاصرة; Sharia Intends; Sunnah; Islamic Economy; Contemporary societies.